DETERMINANT OF TAX AUDIT QUALITY WITH AUDIT ENVIRONTMENT AS MEDIATORS - Rio Eryco Vebriadi; Sabaruddin Sabaruddin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study examines the determinants of tax audit quality by integrating input, process, and output factors with environmental context as a mediating variable. Data were collected from 129 tax auditors in Jakarta using structured questionnaires and analyzed through PLS-SEM. Results indicate that all factors significantly influence audit quality, with environmental factors showing the strongest effect and acting as a partial mediator. These findings highlight the importance of regulatory clarity and organizational culture in strengthening technical and procedural components, offering practical insights for improving tax audit quality and compliance.